EPILEPSY AND THE STIGMA OF WORKERS IN CONTEMPORARY SOCIETY (Fiep Bulletin - online, 2017)
Epilepsy is a relatively common condition in the general population and one of the diseases most oftentreated by neurology. The epileptic disorder is frequent and affects around 1-3% of the world population. Work occupies acentral place in the dynamics of modern society. The cultural controls unfavorable to the social adjustment of the epileptic(Jones, 1965), make it difficult for him to enter the labor market, aggravated by the growing level of unemployment. Theindividual usually has no work problems; But the mere fact of the existence of epilepsy can influence functional performancefor a number of reasons, there are restrictions on functions considered to be risky, involving danger of accidents to theepileptic, third parties or damage of valuable material assets. A historical view about epilepsy allows us to verify the multiplicityof causes that, at their heart, lead to various forms of exclusion and social control of epileptics. In this sense, the need arises toobserve the identification in the work spaces in relation to the worker with epilepsy and which psychosocial aspects emergefrom the objective and subjective identity. It is intended to present occupational status of a sample of epileptic individuals, andto identify the factors that limit their access to the labor market, taking into account the intrinsic and extrinsic factors.
Keywords: epilepsy; stigma; society